Nurse manager responsibilities to address the delineated influences on the experiences of healthcare professionals during COVID-19: A qualitative systematic review nurse managers' role during COVID-19 - Yvonne Botma; Lizeth Roets (Elsevier, 2023)
Aim: With this qualitative research synthesis, we aim to interpret qualitative research findings across multiple studies worldwide to delineate the influences on the mental health of healthcare professionals during the COVID-19 pandemic and deduce the impact on managerial responsibilities. Background: At the hospital level, managers focused on establishing designated COVID-19 wards, ensuring sufficient nurses to replace those who became ill and training staff on patient management issues, but neglected the mental well-being of staff. Methods: A systematic process was followed to search for qualitative studies that answered the research question of what influenced healthcare professionals' experiences during the Covid-19 pandemic. Data were charted literatim from the selected articles. Collaborative content coding occurred iteratively through several coding levels. Results: The unfamiliarity of the disease, deployment, personal protective equipment (PPE), patients, emotions and psychological reactions, and self-care interventions influenced the front-line workers' experiences of the pandemic. In most instances, the nurse managers did not address the experiences comprehensively. Conclusion: It is clear from the findings that many negative influences on healthcare professionals' experiences during the Covid-19 pandemic contributed to mental distress, which may have long-term effects on the healthcare workforce. Implications: Local-level nurse managers could reduce the magnitude of the negative influences on healthcare professionals.